Crossing the threshold of eternity : what the dying can teach the living - Wise, Robert L. (New York : Guideposts, 2007)
An archbishop in the Communion of Evangelical Episcopal Churches explores the topic of death through powerful stories and assures Christians that there is life beyond the grave.
Discovering the picture album -- Learning from the pictures -- Using the pictures.
Includes bibliographical references.
Keywords: Death -- Religious aspects -- Christianity; Death -- Religious aspects -- Christianity